Tingkat Pemberian Empulur Sagu yang Difermentasi dengan Kapang Aspergillus niger Terhadap Persentase Karkas Itik Serati Umur 8 Minggu - Achmad Jaelani; Muhammad Irwan Zakir; Kusyanti Kusyanti (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
The experiment was aimed to know the level of fermented sago by using Aspergillus niger to dressed carcass percentage of Serati duck 8 weeks age. This experiment was used Completely Randomized Design with 5 treatments and 4 replicates (control, 10% 20%, 30% and 40% of fermented sago). Data was analyzed by using analysis of variance and followed by Duncann Multirange test. The Optimal use of fermented sago in diets was 20%. Fermented sago can be applied up to 30% in diets, without decreasing the performance of body weight, dressed carcass weight, and dressed carcass percentage of Serati duck 8 weeks age